The Effect Of Price Policy And Experiential Marketing On Repurchase Intention Mediated By Customer Satisfaction (Study at PT. Maybank Indonesia Finance Regional Jakarta) - Steven; Hery Winoto Tj; Eka Desy Purnama (International Journal of Science, Technology & Management, 2021)
The increase in the number of motorized vehicles can be seen from the data released by the Central Statistics Agency (BPS) explaining that in 2019 the number of vehicles spread in Indonesia reached more than 133 million units where this number increased by around 5.3% compared to the previous two years. The distribution of the total number of vehicles consists of motorcycles, private cars, freight cars and buses. Of the total number of vehicles circulating in Indonesia in 2020, DKI Jakarta contributed about 17% or 20 million vehicles to the total, where the number of vehicles also increased very significantly compared to the previous year. Another surprising fact is that the number of vehicles circulating in Jakarta exceeds the population of Jakarta based on population census data in 2020 which only reached 10.56 million people. However, in 2020 a decline in sales in new car transactions due to the Covid-19 pandemic was also unavoidable so that it became a challenge for PT Maybank Indonesia Finance, especially for customers who had already made transactions, of course, to maintain retention from these customers so that the intention to make transactions emerged. /buyback through PT Maybank Indonesia Finance, which this requires appropriate and effective strategies. This research is a quantitative study with 111 respondents spread across DKI Jakarta, using SMARTPLS 3.3 data processing. The results of the study show that all of the hypotheses studied in this study have a significant influence, so that PT Maybank Indonesia Finance must pay attention to many things to maintain customer retention for re-transactions.